A new species of Karekizo Morimoto, 1962 (Coleoptera: Curculionidae: Molytinae) from the Alishan Mountains of Taiwan and a first record of Karekizo impressicollis outside Japan - Lewis, Jake H. (Zootaxa, 2023)
Karekizo Morimoto, 1962 represents a rarely collected, mountain-dwelling genus which has hitherto been known only from one species, K. impressicollis Morimoto, 1962, in Japan. Here, a second species, Karekizo depressus sp. n., is described based on a single specimen collected from Fen-Chi-Hu, Chiayi Hsien, Taiwan. The type species, K. impressicollis, is reported for the first time outside of Japan, from South Korea (Jeju Island, Mt. Hallasan). X-ray microtomography is used to non-destructively compare the sub-scale cuticular structure (e.g., density of punctures, presence of tubercles or carinae) of the two species. A photographic key to the species is also presented.